Visual symptoms and nutritional deficiencies in olive trees under subjected to nutrient deprivation - Rafael Pio; Filipe Bittencourt Machado de Souza; Viviane Amaral Toledo Coelho; Cleber Lázaro Rodas; Inêz Pereira da Silva; Evaldo Tadeu de Melo (Acta Scientiarum. Agronomy, 2019)
Brazil is one of the largest importers of olive (Olea europaea L.) products, being the fourth largest importer of olive oil and the fifth of olives. In recent decades the introduction and growing of olive cultivars less chilling requirement in the South and Southeast made viable the olives production in the country. On the other hand, there are still shortages of information about the management of this crop in our country, especially in relation to studies about the nutritional needs of the olive tree, grown in subtropical regions, and it may enable advances in productivity of this fruit. The aim of study was to evaluate the growth, dry matter production and nutritional status of the olive tree under the effect of the omission of nutrients as well as establish visual diagnosis parameters. We used a completely randomized design with ten treatments and three repetitions, corresponding to growing in Hoagland – Arnon nutrient solution, and solutions with individual omissions of N, P, K, Ca, Mg, S, B, Fe and Zn. Omission of nutrients that most limit the growth of the olive tree are N, Ca and B. Deficiencies of nutrients in olive seedlings presented by typical symptoms.